Characterization of PAX‐21 Insensitive Munition Detonation Residues. Issue 3 (2nd May 2013) - Walsh, Michael R.; Walsh, Marianne E.; Taylor, Susan; Ramsey, Charles A.; Ringelberg, David B.; Zufelt, Jan E.; Thiboutot, Sonia; Ampleman, Guy; Diaz, Emmanuela
Abstract Insensitive high explosives are being used in military munitions to counteract unintended detonations during storage and transportation. These formulations contain compounds such as 2, 4‐dinitroanisole (DNAN) and 3‐nitro‐1, 2, 4‐triazol‐5‐one (NTO), which are less sensitive to shock and heat than conventional explosives. We conducted a series of four tests on snow‐covered ice utilizing 60‐mm mortar cartridges filled with 358 g of PAX‐21, a mixture of RDX, DNAN, and ammonium perchlorate. Rounds were detonated high‐ and low‐order using a fuze simulator to initiate detonation. Blow‐in‐place (BIP) operations were conducted on fuzed rounds using an external donor charge or a shaped‐charge initiator. Results indicate that 0.001 % of the original mass of RDX and DNAN were deposited during high‐order detonations, but up to 28 % of the perchlorate remained. For the donor block BIPs, 1 % of the RDX and DNAN remained. Residues masses for these operations were significantly higher than for conventional munitions. Low‐order detonations deposited 10–15 % of their original explosive filler in friable chunks up to 5.2 g in mass. Shaped‐charge BIPs scattered 15 % of the filler and produced chunks up to 15 g. Ammonium perchlorate residue masses were extremely high because of the presence of large AP crystals, up to 400 μm in the recovered particles.